Sodium butyrate alleviates DSS-induced inflammatory bowel disease by inhibiting ferroptosis and modulating ERK/STAT3 signaling and intestinal flora - Yingyin Liu; Nachuan Chen; Huaxing He; Lulin Liu; Suxia Sun (Annals of Medicine)
Background Inflammatory bowel disease (IBD), encompassing Crohn’s disease (CD) and ulcerative colitis (UC), can seriously impact patients’ quality of life. Sodium butyrate (NaB), a product of dietary fiber fermentation, has been shown to alleviate IBD symptoms. Some studies have shown that it is related to ferroptosis. However, the precise mechanism linking NaB, IBD, and ferroptosis is not clear.Objective This study aimed to demonstrate that NaB suppresses ferroptosis, thereby alleviating inflammatory bowel disease (IBD) through modulation of the extracellular regulated protein kinases/signal transducer and activator of transcription 3 (ERK/STAT3) signaling pathway and intestinal flora.Methods An IBD model was established using 2.5% (w/v) dextran sulfate sodium (DSS). Mice were orally administered low-dose NaB, high-dose NaB , or 5-aminosalicylic acid (5-ASA). Ferroptosis-related molecules were measured using specific kits, and western blotting (WB) and real-time polymerase chain reaction (RT-qPCR) were used to determine the levels of the target molecules.Results NaB alleviated symptoms in IBD mice, including reduced weight loss, prolonged colon length, reduced disease activity index (DAI), and reduced spleen index and mRNA expression of inflammatory factors. Additionally, NaB reduced the content of Fe2+ and myeloperoxidase (MPO) and increased the content of GSH and the activity of superoxide dismutase (SOD), which reflected NaB-inhibited ferroptosis. Moreover, western blotting showed that NaB enhanced STAT3 and ERK phosphorylation. In addition, NaB regulates the composition and functions of flora related to IBD.Conclusion NaB alleviates IBD by inhibiting ferroptosis and modulating ERK/STAT3 signaling and the intestinal flora.KEYWORDS Sodium butyrate; IBD; ferroptosis; STAT3; ERK; gut microbiota